Separation and Recovery of Cadmium(II) from Wastewater of Zinc Mining by Using Hollow Fiber Supported Liquid Membrane - S. Treephaiboon; U. Pancharoena; A. W. Lothongkumb (My University, 2017)
The extraction and recovery of cadmium(II) via a hollow fiber supported liquid membrane (HFSLM) containing D2EHPA as a carrier dissolved in kerosene. The various effects on extraction and recovery cadmium were studied pH of feed phase, concentration of extractant and pH of stripping phase. The extraction and recovery of cadmium by using the hollow fiber supported liquid membrane method were 97% and 57%, respectively. The transport of cadmium ions was achieved by driving force of the concentration gradient. The behavior of extraction and/or recovery in HFSLM could be demonstrated in mass-transfer coefficient among feed phase, membrane phase and stripping phase. Determining the limiting step controlling the mass transfer of cadmium ion used the permeability coefficient.
Keywords: Stripping (fiber); Hollow fiber membrane; Mass transfer coefficient; Kerosene; Liquidliquid extraction; Membrane Technology; Extraction and Separation Processes